The Effect of Communication and Brand Trust on Sustainable Commitment - Bursan, Rinaldi (Jurnal Ilmiah Manajemen Kesatuan, 2024)
In the modern era, cycling communities have become a means for people to interact and share experiences, as well as to build trust in certain bicycle brands. This study aims to analyze the influence of community and brand trust on the commitment of cycling community members in Bandar Lampung. This research uses a quantitative method with data collected through questionnaires distributed to members of the cycling community in Bandar Lampung. The number of samples used was 50 samples. The collected data were analyzed using linear regression techniques to determine the extent of the influence of community and brand trust on member commitment. The results of the study show that the community has a positive and significant impact on member commitment. Members who feel connected and supported by the community are more likely to show a high commitment to cycling activities and the brands they use. Additionally, brand trust has also been shown to have a significant effect on commitment. Community members who have high trust in the quality and reputation of the brand are more likely to exhibit sustained commitment. These findings underline the importance of building a strong community and enhancing brand trust as strategies to increase customer commitment in the bicycle industry. This research provides significant contributions for marketers and bicycle manufacturers in formulating effective marketing strategies by leveraging community aspects and brand trust.